Efficacy of intraoperative cholangiography versus preoperative magnetic resonance cholangiography in patients with intermediate risk for common bile duct stones. Issue 11 (November 2022) - Staubli, Sebastian M.; Kettelhack, Christoph; Oertli, Daniel; von Holzen, Urs; Zingg, Urs; Mattiello, Diana; Rosenberg, Robert; Mechera, Robert; Rosenblum, Ilan; Pfefferkorn, Urs; Kollmar, Otto; Nebiker, Christian A.
Abstract: Background: This is the first randomized trial to evaluate the efficacy of intraoperative cholangiography (IOC) and magnetic resonance cholangiopancreatography (MRCP) in patients with suspected CBDS. Methods: This unblinded, multicenter RCT was conducted at five swiss hospitals. Eligibility criteria were suspected CBDS. Patients were randomized to IOC and laparoscopic cholecystectomy (LC), followed by endoscopic retrograde cholangiopancreatography (ERCP) if needed, or MRCP followed by ERCP if needed, and LC. Primary outcome was length of stay (LOS), secondary outcomes were cost, stone detection, and complication rates. Results: 122 Patients were randomised to the IOC Group (63) or the MRCP group (59). Median LOS for the IOC and the MRCP groups were 4 days IQR [3, 6] and [4, 6], with an estimated increase of LOS of 1.2 days in the MRCP group ( p = 0.0799) in the linear model. Median cost in the IOC and MRCP groups were 10 473 Swiss Francs (CHF) and 10 801 CHF, respectively ( p = 0.694). CBDS were found in 24 and 12 patients in the IOC and the MRCP groups, respectively ( p = 0.0387). The complication rate did not differ between both groups. Conclusion: There is equipoise between both pathways. IOC has a significantly higher diagnostic yield than MRCP. Trial registration: Clinicaltrials.gov identifier NCT02351492: Radiological Investigation of Bile Duct Obstruction (RIBO). Graphical abstract: Image 1